Pengembangan E-LKPD Berbasis Preview, Question, Read, Reflect, Recite, Review (PQ4R) Pada Materi Kesetimbangan Ion dan pH Larutan Penyangga - Rery, R. Usman; Erviyenni, Erviyenni; Hardiyansyah, Muhammad Agus (Universitas Negeri Semarang, 2023)
The development of PQ4R-based electronic activity sheet on the subject of ionic equilibrium and pH of buffer solutions aims to develop a valid electronic activity sheet and determine user responses in learning. The research method used is the research and development (RD) method by applying a 4D development model which includes Define, Design, Develop and Disseminate, pandemic conditions that cause research to only be carried out until the Develop stage which was followed by one-on-one trials, teacher trials and limited trials. The data collection tools used are validity sheets and user response questionnaires. The data analysis technique used is to calculate the results of the validation assessment and user responses. The results of the study explain that the developed PQ4R-based electronic activity sheet has been categorized as